Anticorrosion Properties Of Epoxy Zinc Oil Palm Frond Cellulose Nanocrystal Composite Coating For Mild Steel Corrosion Protection - Azani, Nur Fatin Silmi Mohd (2021)
Epoxy zinc (epoxy-Zn) coating has been widely used as corrosion protection. However, the high porosity of epoxy-Zn is tend to drawback the barrier properties of the coating. Thus, the surface modification of epoxy-Zn is imperative. This study focused on effect of oil palm frond cellulose nanocrystal (OPF-CNC) as a reinforcing nanofiller to improve epoxy-Zn barrier properties. In this work, OPF biomass was utilised in preparing OPF-CNC by H2SO4 hydrolysis. OPF was initially pre-treated with autohydrolysis pre-treatment. The surface analyses via transmission electron microscopy (TEM) confirmed that the OPF-CNC is a nanofiller with an average length and diameter of 95.09 and 6.81 nm, respectively. The anticorrosive performance of epoxy-Zn coating and modified epoxy-Zn coating was investigated using electrochemical analyses via electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (PD) and open circuit potential (OCP). The anticorrosive performance and surface properties of modified epoxy-Zn (E-Zn-0.5) were compared with commercial zinc chromate paint. It was revealed that E-Zn-0.5 has higher inhibition efficiency (99 %) than commercial paint (70 – 80 %). Based on wettability study, E-Zn-0.5 shows the highest hydrophobicity (100.5 ± 0.70°) than commercial paint (91.04 ± 1.20°). The hardness test revealed that the coating’s hardness value for E-Zn-0.5 is higher than commercial paint of 0.61 and 0.25 GPa, respectively. Thus, the improved corrosion protection properties of epoxy-Zn with the addition of OPF CNC proof the potential of OPF biomass waste to be utilized as an alternative in renewable green materials.